Analisis Keputusan Pembelian pada Konsumen Warung Kopi Nilang - Ayu Dewi Hemayani; Efrina Masdaini (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2022)
This study aims to determine the strategies and constraints in marketing at the Nilang coffee shop. the type of research used is a qualitative research with a descriptive type of research. The results of this study indicate that the coffee shop has implemented a marketing mix strategy that uses the 4p variable nemely: product, price, place, and promotion which can increase profits and sales of their products. In this study, there are also supporting factors and inhibiting factors for implementing the marketing mix strategy on product sales, which are supporting factors, namely support from the community, good service, and advances in technology. while the inhibiting factor is that the nilang coffee shop is often visited by buskers and beggars because the place is open, in addition to disturbing the peace and comfort of visitors. The lack of awareness of time consistency and discipline is what makes marketing at the nilang coffee shop less successful. Â